Skull Base Meningiomas: Is Surgical Resection Enough? Outcome Evaluation and Prognostic Factors Analysis in a Single-Center Cohort - Pessina, Federico; Navarria, Pierina; Rossini, Zefferino; Clerici, Elena; Fornari, Maurizio; Politi, Letterio S.; Scorsetti, Marta; Servadei, Franco (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Surgical resection represents the mainstay of treatment in skull base meningiomas (SBMs). Considering the high recurrence rate reported, an adjuvant radiation therapy (RT) treatment should be considered. The aim of this study was to evaluate the progression-free survival (PFS), overall survival (OS), and prognostic factors conditioning outcome.Methods Patients receiving surgical resection for grade I SBMs were included. The extent of resection (EOR) was dichotomized as gross total resection (GTR) and subtotal resection (STR). RT was administered only in patients receiving STR. Clinical outcome was evaluated by brain magnetic resonance imaging (MRI) performed every 6 months for the first year and yearly thereafter.Results From January 2000 to December 2015, 123 patients were treated. The majority were females (70.7%), with a Karnofsky Performance Score (KPS) ≥80 (95%), and symptoms at diagnosis (91%). GTR was performed in 30% of cases and STR in 70%. RT was performed in 18 (20.9%) patients at diagnosis and in 29 (33.7%) patients at progression. Improvement or stability of neurologic status was obtained in 78.9% of patients. The median follow-up time was 91 months (range: 40–230 months). Local recurrence occurred in 34 (27.6%) patients at a median time of 45 months (range: 6–214 months). The median, 2-, 5-, and 10-year PFS were 193 months, 89.3, 81.8, and 72.5%, respectively. On univariate and multivariate analyses, factors impacting on PFS were EOR, tumor location, neurologic postoperative status, and adjuvant RT in STR.Conclusions A safe surgical resection followed by RT adjuvant treatment could represent the better choice to obtain local control maintaining neurologic integrity. Our data underlined the value of adjuvant RT in incompletely resected meningiomas.
Keywords: skull base meningiomas; surgery; prognostic factors